Exploiting Phase-Change Memory in Cooperative Caches - Ramos, Luiz; Bianchini, Ricardo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2012)
Modern servers require large main memories, which so far have been enabled by improvements in DRAM density. However, the scalability of DRAM is approaching its limit, so Phase-Change Memory (PCM) is being considered as an alternative technology. PCM is denser, more scalable, and consumes lower idle power than DRAM, while exhibiting byte-address ability and access times in the nanosecond range. Unfortunately, PCM is also slower than DRAM and has limited endurance. These characteristics prompted the study of hybrid memory systems, combining a small amount of DRAM and a large amount of PCM. In this paper, we leverage hybrid memories to improve the performance of cooperative memory caches in server clusters. Our approach entails a novel policy that exploits popularity information in placing objects across servers and memory technologies. Our results show that (1) DRAM-only and PCM-only memory systems do not perform well in all cases, and (2) when managed properly, hybrid memories always exhibit the best or close-to-best performance, with significant gains in many cases, without increasing energy consumption.